1975
DOI: 10.1017/s0021859600062481
|View full text |Cite
|
Sign up to set email alerts
|

Marginal sulphur supplies for grassland herbage in south-east Scotland

Abstract: Sulphur deficiency in agricultural crops has never been regarded as a significant problem in Great Britain. However, the widespread use of sulphurfree fertilizers and the introduction of Clean Air Acts together with increased crop yields necessitate a reappraisal of the situation. S.E. Scotland is an area where atmospheric sulphur dioxide levels are considerably lower than most other regions of Britain (Junge, 1972). The concentration of sulphur in precipitation is also relatively low (Stevenson, 1968) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The hydrogen sulphide formed was measured by the methylene blue method.6 Total sulphur in the soils was estimated in the same way after ignition at 400°C with silver oxide and sodium bicarbonate to oxidise organic sulphur to sulphate.7 The sulphate retention capacity of the soils used in the pot experiment was measured as described by Scott. 8 Free iron and aluminium were extracted by the acid oxalate m e t h~d ,~ iron being determined with 2: 2l dipyridyl and aluminium by the Aluminon method.10 Carbon was determined by the Walkley-Black method.ll…”
Section: Soil Analysesmentioning
confidence: 99%
“…The hydrogen sulphide formed was measured by the methylene blue method.6 Total sulphur in the soils was estimated in the same way after ignition at 400°C with silver oxide and sodium bicarbonate to oxidise organic sulphur to sulphate.7 The sulphate retention capacity of the soils used in the pot experiment was measured as described by Scott. 8 Free iron and aluminium were extracted by the acid oxalate m e t h~d ,~ iron being determined with 2: 2l dipyridyl and aluminium by the Aluminon method.10 Carbon was determined by the Walkley-Black method.ll…”
Section: Soil Analysesmentioning
confidence: 99%
“…The results of studies carried out in recent years in Britain have suggested that grassland herbage in some regions may be unable to obtain sufficient sulphur (S) to support optimum plant growth (McLaren, 1975;Williams, 1975 this is likely to occur include areas where soil reserves of S are low (both as sulphate and organic S), atmospheric inputs are small, only S-free fertilizers are used and high rates of nitrogen (N) are applied.…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies carried out in recent years in Britain have suggested that grassland herbage in some regions may be unable to obtain sufficient sulphur (S) to support optimum plant growth (McLaren, 1975;Williams, 1975…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, these measurements were too variable in relation to apparent crop requirement to provide information about the S status of the crop, both for deficient (McLaren 1975) and excess (Rennenberg 1984) situations. Part of the problem could be that these measurements vary considerably with the plant's stage of growth, the tissue sampled (Kelling and Matocha 1990), or even the method of S measurement (Kowalenko 2000).…”
Section: Discussionmentioning
confidence: 89%